A techno-economic analysis of solar catalytic chemical looping biomass refinery for sustainable production of high purity hydrogen. (1st September 2021) - Sajjadi, Baharak; Chen, Wei-Yin; Fan, Maohong; Rony, Asif; Saxe, Jennie; Leszczynski, Jerzy; Righetti, Tara K.
Graphical abstract: Highlights: A solar catalytic chemical looping biomass refinery (SCCLBR) power plant was modelled. The focal point of the plant is the chemical looping process and integrated pyrolysis/gasification. Ca2 Fe2 O5 was considered as the oxygen carrier catalyst of the chemical looping process. The reduced form of Ca2 Fe2 O5 (CaO and Fe 0 ) can be regenerates using CO2 at temperatures above 730 °C. The CCLBR and integrated SCCLBR can reach the efficiency of 34% and 41%, respectively. Abstract: Compared to traditional biomass and coal-fired power plants, a process that includes integrated pyrolysis and subsequent gasification is a promising technology to deliver a larger electrical output through the production of high-purity hydrogen with a low carbon footprint. Chemical looping can further enhance the biomass contribution to the global renewable energy demand while fulfilling the stringent CO2 emission cuts needed in the energy sector. This study aims at investigating the feasibility of developing a solar catalytic chemical looping biomass refinery (SCCLBR) power plant for sustainable production of energy using a comprehensive plant modeling and techno-economic assessment. The plant is composed of 7 sequential units: i) biomass preparation (drying, transferring, and grinding), ii) reacting unit (SCCLBR), iii) water gas shift unit and heat recovery, iv) CO2 and H2 S separation (Rectisol Process), v) sulfur removal (Claus Process), vi) air separation and vii) catalyst regeneration. The simulation was performed for 1–6 tonne/hour of biomass as input. The effect of key variables (feedstock load, water injection, and temperature) on the economic performance of the plant were analyzed. The simulated results of the chemical looping reactor were validated against the experimental results, while the results of Rectisol and air separation units were validated against the thermodynamic simulation. The results demonstrated that the CCLBR (without solar integration) and integrated SCCLBR can reach the efficiency of 34% and 41% respectively, yet the results have not been optimized. The sensitivity analysis indicated that water injection rate is the most influential parameter, which can even suppress the impact of biomass loading rate. A separate thermodynamic simulation was also performed to investigate the reaction equilibrium of oxygen carrier regeneration (Ca2 Fe2 O5 ) using CO2 . The results demonstrated that a temperature above 730 °C is required to avoid carbonation (Fe2 O3 and CaCO3 production). The maximum greenhouse gas emission in SCCLBR is 10.70, which is significantly lower than traditional coal-to-hydrogen and biomass-to-hydrogen power plants. It has also been found that across varying feedstock input rates, greenhouse gas emissions average 12.8% lower when solar PV supplements refinery power needs; optimization of the steam/biomass ratio may reduce emissions even further.